Rac(e)ing to computer science for all: how teachers talk and learn about equity in professional development. Issue 3 (3rd July 2021) - Goode, Joanna; Ivey, Allison; Johnson, Stephany RunningHawk; Ryoo, Jean J.; Ong, Christine
ABSTRACT: Background and Context : Though computer science education is marked by a pronounced racial participation gap, there is little research about effective ways that teachers can be supported in creating racially-just and equitable computer science learning opportunities for students. Objectives : This paper examines how teachers engage in learning about race and equity in computer science education during professional development. Method : Drawing from data collected from 94 participants attending a summer week-long Exploring Computer Science workshop, this mixed-methods study revealed how key curricular and instructional features of professional development foster race-conscious discussions and shifts in beliefs and agency around broadening participation in computing. Findings : Given the importance of developing teacher capacity to increase opportunities for students of color in computing classrooms, the findings of this study highlight how intentionally integrating race education in the center of professional development for teachers can support teachers' equity-based beliefs and practices. Implications : Professional development for teachers that seeks to broaden participation in computing is supported by long-term professional learning that explicitly center issues of race and equity in the curriculum.